Otwarta i zamknięta opieka zdrowotna w Zielonej Górze w latach 1945-1989 = Open and closed health care in Zielona Gora in 1945-1989 - Kotula, Jacek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
During the period of 1945-1989 there was a systematic development of an open and closed health care in Zielona Gora. The increasing number of citizens needed continual increasment of the figure of medical personnel that was able to fulfill the health needs of the population as well as health care infrastructure. The medical establishments due to the costs of health care underestimation fought with living conditions difficulties.
Keywords: opieka zdrowotna; Zielona Góra; lecznictwo; heath care; therapeutics